Contributions of carbon source, crop cultivation, and chemical property on microbial community assemblage in soil subjected to reductive disinfestation - Zhu, Weijing; Lu, Xiaolin; Hong, Chunlai; Hong, Leidong; Zhu, Fengxiang; Zhang, Shuo; Yao, Yanlai (Frontiers in Microbiology, 2023)
In agricultural practice, reductive soil disinfestation (RSD) is an effective method for eliminating soil-borne pathogens that depends heavily on carbon source. However, knowledge regarding the assembly of soil microbial communities in RDS-treated soils amended with different carbon sources after continuous crop cultivation is still not well-characterized. RSD treatments were performed on greenhouse soil with six different carbon sources (ethanol, glucose, alfalfa, wheat bran, rice bran, and sugarcane residue), which have different C:N ratios (Org C/N) and easily oxidized carbon contents (Org EOC). After RSD, two consecutive seasons of pepper pot experiments were conducted. Then, the effects of carbon source property, crop cultivation, and soil chemical property on soil microbial community reestablishment, pathogen reproduction, and crop performance were investigated in the RSD-cropping system. Variation partition analysis indicated that carbon source property, crop cultivation, and soil chemical property explained 66.0% and 39.0% of bacterial and fungal community variation, respectively. Specifically, Mantel tests showed that Org C/N, crop cultivation, soil available phosphorus and potassium were the most important factors shaping bacterial community composition, while Org C/N, Org EOC, and crop cultivation were the most important factors shaping fungal community composition. After two planting seasons, the number of cultivable Fusarium was positively correlated with Org EOC, and negatively correlated with soil total organic carbon, Fungal Chao1, and Fungal PC1. Crop yield of complex-carbon soils (Al, Wh, Ri and Su) was negatively affected by Org C/N after the first season, and it was highest in Al, and lower in Et and Su after the second season. Overall, Org EOC and Org C/N of carbon source were vitally important for soil microbe reestablishment, Fusarium reproduction and crop performance. Our findings further broaden the important role of carbon source in the RSD-cropping system, and provide a theoretical basis for organic carbon selection in RSD practice.